Spatial distribution and abondance of freshwater snails in Lake Kivu, DR Congo side - Jean-Jacques M. Bagalwa; Pierre C. Batumike; Bertin K. Ndegeyi; Jean-Louis K. Bahizire (European Scientific Journal, ESJ, 2024)
The main goal of this investigation was to study the distribution of freshwater molluscs in Lake Kivu located in DR Congo side. Mollusca play important role in the public and veterinary health and thus need to be study their distribution continuously. The semi-quantitative surveys carried out during the period of January 2019 to December 2019 has focused on sites selected in lake covering the dry and wet seasons. The choice of these sites was based on the molluscan data available, physical structure of the littoral and structure associated vegetation. The harvesting of snails in the littoral zone of Lake Kivu was done using a plankton net and pliers. The physicochemical parameters of the water at each site were carried out using the standard water quality analysis method. The collected snails were morphologically identified using different identification keys. Biomphalaria species were analyzed for trematode infestation. One thousand three hundred and thirty-six (1,356) snails belonging to seven genera and seven species were recorded during the study. The overall relative percentage of the various snail species recorded was: Biomphalaria pfeifferi (50.8 %), Biomphalaria smithi (13.1 %), Gabbielle spirilosa (11.2 %), Bulinus tuncatus (10.2 %), Lymnea natalensis (5.7 %), Helisoma duryi (2.5 %), Pila ovata (1.4), Melanoides tuberculata (1.2%), Lymnea columella (0.7 %), Tomchia hendrexyx (0.6 %), Bulinus forskalii (0.5 %), Tomchia ventricosa and Physa acuta (0.4 %), Tomchia zwellandanensis, Corbicula fluminalis and Hydrobia accrensis  (0.3 %), Lymnae palutris (0.2 %), Tomchia kivuensis and Segmentorbis kempi (0.1 %). The present clarified the distribution and seasonal abundance of freshwater snails in Lake Kivu, DRCongo side. Eighteen species of freshwater snails were collected in the malacological survey in the Lake Kivu, DRC side. The observed snail distribution can provide insight into some aspects of the epidemiology of trematode infection in the study area and the potential risks to humans and animals. The implications of these findings for the control of snail-borne trematodes are also discussed.